'It was supposed to be fair here': Human rights and recourse mechanisms in the Dominican Republic's prison reform process. Issue 1 (1st January 2022) - Peirce, Jennifer
Abstract: This article analyzes prisoners' accounts of human rights violations and protections in two types of prisons in the Dominican Republic: "new" prisons that uphold goals of rights and rehabilitation and "old" prisons that mostly warehouse people. This mixed-methods study finds that prisoners experience significant violence, mostly by other prisoners in old facilities and mostly by corrections staff in new facilities, with different rationales and possible responses. I consider three types of recourse mechanisms: top-down (courts or external commissions), bottom-up (advocacy), and internal institutional (grievance processes and human rights training). I argue that each of these carries constraints, and prisoners perceive official channels to favor the institution. The prevalence of rights violations and the narrow recourse options generate cynicism and frustration among prisoners and their families, which can undermine the legitimacy gained through other important improvements in the reform process.